Production of Gastrointestinal Tumors in Mice by Modulating Latent Transforming Growth Factor Beta 1 Activation - Shibahara, Kotaro (2012)
Transforming growth factor-β (TGF-β) and its signaling pathways are important mediators in the suppression of cancers of the gastrointestinal (GI) tract. TGF-β is released from cells in a latent complex consisting of TGF-β, the TGF-β propeptide (LAP) and a latent TGF-β binding protein (LTBP). We previously generated mice in which the LTBP-binding cysteine residues in LAP TGF-β1 were mutated to serine precluding covalent interactions with LTBP. These Tgfb1(C33S/C33S) mice develop multiorgan inflammation and tumors consistent with reduced TGF-β1 activity. To test whether further reduction in active TGF-β levels would yield additional tumors and a phenotype more similar to Tgfb1(-/-) mice, we generated mice that express TGF-β1(C33S) and are deficient in either integrin β8 or TSP-1, known activators of latent TGF-β1. In addition we generated mice that have one mutant allele and one null allele at the Tgfb1 locus, reasoning that these mice should synthesize half the total amount of TGF-β1 as Tgfb1(C33S/C33S) mice and the amount of active TGF-β1 would be correspondingly decreased compared to Tgfb1(C33S/C33S) mice. These compound mutant mice displayed more severe inflammation and higher tumor numbers than the parental Tgfb1(C33S/C33S) animals. The level of active TGF-β1 in compound mutant mice appeared to be decreased compared to Tgfb1(C33S/C33S) mice as determined from analyses of surrogate markers of active TGF-β, such as P-Smad2, C-Myc, KI-67, and markers of cell cycle traverse. We conclude that these mutant mice provide a useful system for modulating TGF-β levels in a manner that determines tumor number and inflammation within the GI tract.